Managing housing and stocking density to optimize health, welfare and production in pig herds - Hennig-Pauka, Isabel (Burleigh Dodds Series in Agricultural Science, 2023)
This chapter describes major husbandry- and management-related factors affecting health, welfare and production efficiency in different swine husbandry systems. Given the current transformation in pig production, there are several conflicting goals which need to be addressed during design and adaptation of husbandry systems in the future. The following sections deal with the most important areas impacting pig health and welfare such as space, climate, flooring, water and feed supply. Since it is not possible to give a comprehensive overview of all systems the authors summarize fundamental housing requirements which must be achieved in all systems. They also review basic principles in assessing the quality of housing systems. The very important human factor is addressed at the end of the chapter.